SCIENTIFIC APPROACH TO A COMPLEX ASSESSMENT OF DETERMINANTS OF THE INSURANCE MARKET DEVELOPMENT OF UKRAINE - L. V. Popova; N. O. Kovalchuk; D. D. Polagnyn (Фінансово-кредитна діяльність: проблеми теорії та практики)
Variability of economic and political conditions in Ukraine put forward new requirements for assessing the development of the insurance market, the state of which has a significant impact on the activities of economic relations and the state as a whole. Building an adequate model for assessing the insurance market and its practical use may affect the timely adoption of managerial decisions and the development of measures to improve the insurance market functioning. This is confirmed by a large number of scientific studies in the economic literature on the analytical component of the insurance market management, as well as the fact that a timely and objective comprehensive analysis is an integral part of the adoption of effective managerial decisions.